South America, Set of agroclimatic indicators for the identification of abiotic stresses (Base of the subsetting tool) - Mora, Brayan (2022)
The purpose for which these indicators were created is to group or characterize the different accessions available in the Genesys database, considering climatic data from where they were collected. For the above, it is necessary to carry out a characterization of zones based on agroclimatic indicators, which are framed in evaluating the following stresses: Heat, Drought and Flooding, in addition to including indicators that capture the behavior of the photoperiod.